'Business as usual': The Treaty of Lisbon and transnational party manifestos - Ares, Cristina; Volkens, Andrea (Política y Sociedad, 2021)
The Treaty of Lisbon was a milestone in the enduring process of empowerment of the European Parliament and its connections to the European Commission. This latest reform of the Treaties, in force since December 2009, placed the only supranational institution whose members are directly elected by all citizens of the EU (since 1979) on an equal footing with the Council as a co-legislator in around thirty additional policy areas. The Treaty of Lisbon also strengthened the European Parliament in terms of the annual and multiannual budgetary decisions, and it granted it the right to elect the President of the European Commission according to the results of the European elections. This article examines various possible effects of this major boost of the European Parliament, along with links to the European Commission in the manifestos issued by five European parties: the Alliance of Liberals and Democrats for Europe (ALDE), European Free Alliance (EFA), European Green Party (European Greens or EGP), European People’s Party (EPP), and Party of European Socialists (PES). It studies variations from 2004 onwards in the scope of the programmatic proposals regarding EU domains of power, the footprint in the manifestos of the transnational party organisations themselves, and eventually also of their candidates for the presidency of the European Commission. To do so, the twenty manifestos issued by the abovementioned parties for the 2004, 2009, 2014 and 2019 European elections were content analysed. The results point to the lasting distance between these transnational parties and the European elections, despite the reinforcement of the role of the European Parliament over time.
Keywords: European Parliament; European parties; ALDE; EFA; EGP; EPP; PES